Cracking the Glass Ceiling: The Case of Women’s Empowerment in Promoting Village Tourism Development in Malang, Indonesia - Budi Hendrarti, Dwi Windyastuti; Wasis Lestari, Kalimah; Faridha Wardhani, Nuke; Ravindra Thakare, Bhushan (JSP (Jurnal Ilmu Sosial dan ilmu Poltik), 2024)
This study analyses how the Family Empowerment and Welfare Mobilization (PKK) team plays a significant role in increasing village tourism development in Pujon Kidul, Malang Regency, East Java Province, Indonesia. We highlighted women's empowerment by categorising the social, economic, and political dimensions that contribute to the success. Using the case study method, we investigated the phenomenon in tourism development from 2011 to 2023 (12 years). Data was collected through in-depth interviews with key stakeholders to reveal the extent to which women have been “cracking their glass ceiling” in the three dimensions. The finding reveals that the PKK team could accommodate women's interests and actualise their aspirations and initiatives by promoting community movement (social dimension), allowing them to join SMEs and upskilling programs (economic dimension), and involving them in drafting village development plans and budgeting (political dimension). This study contributes to the literature on women’s empowerment, especially in the social, economic, and political dimensions of tourism development.